Implementation Of a Web-Based Queuing System in Hospital Polyclinic Services Using the FIFO Method: Case Study of Karangpawitan Community Health Center - Naufal, Mochammad; Marjito, Marjito; Komarudin, Komarudin (Informatics Management, Engineering and Information System Journal, 2023)
This study uses a web-based queueing system to enhance efficiency in hospital outpatient clinics by employing the First-In, First-Out (FIFO) approach. The implemented technology is seamlessly incorporated into the preexisting hospital information system to streamline the operations of registration and queue monitoring. The First-In, First-Out (FIFO) method will be utilized to forecast the number of incoming patients and approximate service durations using previous data from outpatient services. By employing this approach, the hospital is anticipated to optimize resource allocation, minimize patient waiting periods, and improve patient contentment. This study will employ software development methodologies such as requirement analysis, system design, implementation, and assessment. Data collection will be carried out using observation, interviews, and current system documentation. The findings of this study are expected to enhance the standard of treatment in hospital outpatient clinics and guide other healthcare organizations in deploying web-based queueing systems utilizing the FIFO method. This research aims to enhance comprehension of the advantages and obstacles of implementing a web-based queueing system in healthcare services.